Our struggle for self ; Coming to Palawan ; Discovering Guimaras [videorecording] - Lazaro, Cheche (Quezon City Probe Productions, 1994)
Summary: Documents the Asia-Pacific Conference on East Timor; the migration of people in Palawan; and the mango plantation in Guimaras, Iloilo.
Contents: Our struggle for self (20 min.)--Coming to Palawan (30 min.)--Discovering Guimaras (12 min.).
VHS.
Credits: Reporters, Marga Ortegas, Cheche Lazaro, Luchi Cruz-Valdes.
Keywords: Migration, Internal -- Philippines -- Palawan; Mango industry -- Philippines -- Guimaras Island